FMCW radar for slow moving target detection: Design and performance analysis - Muhd Ariffin, Nor Fatin; Mohd. Isa, Farah Nadia; Ismail, Ahmad Fadzil (IEEE, 2016)
This paper discusses the design and performance of a Frequency Modulated Continuous Wave (FMCW) Radar Doppler for slow moving target detection. It is modeled as a lowcost and feasible radar remote sensor for measuring particular moving target’s range and velocity. It operates at ISM band with a center frequency of 2.4GHz, transmit power of approximately 11.3dBm and 52MHz transmit signal bandwidth. The radar also employs linear FM waveform, bistatic antenna system, and Doppler mode operation. The radar hardware architecture is built by assembling off-shelf electronic devices and tested towards slow moving target in a Microwave Laboratory. The target that is used to evaluate and analyze the radar performance is a human body which moves at different speeds over time. The analysis demonstrates that the proposed radar system capable of detecting and measuring the target’s velocity and range. Besides, the radar system demonstrates that it can measure min velocity of 0.77 m/s for the short range moving target.